2016
DOI: 10.1208/s12249-016-0599-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Bosentan and Selected PDE-5 Inhibitors in the Design of Drugs for Rare Diseases

Abstract: Abstract.The study provides the physicochemical characteristic of bosentan (BOS) in comparison to tadalafil (TA) and sildenafil citrate (SIL). Despite some reports dealing with thermal characteristic of SIL and TA, physicochemical properties of BOS have not been investigated so far. Recent clinical reports have indicated that the combination of bosentan and PDE-5 inhibitor can improve the effectiveness of pharmacotherapy of pulmonary arterial hypertension (PAH). However, in order to design personalized medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…The raw BST showed endotherm peak at 111.6 °C. The peak at 111.6 °C represents the melting point of BST, indicating that a high crystalline solid state is achieved [ 32 ] and the peak of the dehydration of the hydrated form was overlapped by melting peak. However, the solid state of SD formulations was extremely transformed by spray drying.…”
Section: Resultsmentioning
confidence: 99%
“…The raw BST showed endotherm peak at 111.6 °C. The peak at 111.6 °C represents the melting point of BST, indicating that a high crystalline solid state is achieved [ 32 ] and the peak of the dehydration of the hydrated form was overlapped by melting peak. However, the solid state of SD formulations was extremely transformed by spray drying.…”
Section: Resultsmentioning
confidence: 99%
“…The partition coefficient (Log P) of TDF is 1.54, which reflects poor drug solubility in water. 23 Many approaches have been tested and described in the literature to increase the dissolution rate and bioavailability of TDF. The approaches reported include the use of (1) inclusion complexes, 24 (2) solid dispersion, 25−27 (3) amorphous hot-melt extrudate, 28 (4) nanosuspension, 29 and (5) crystalline solvates forms.…”
Section: Introductionmentioning
confidence: 99%
“…TDF is a neutral drug with p K a of 15.17. The partition coefficient (Log P) of TDF is 1.54, which reflects poor drug solubility in water . Many approaches have been tested and described in the literature to increase the dissolution rate and bioavailability of TDF.…”
Section: Introductionmentioning
confidence: 99%
“…This has the advantage of examining both fasted and fed states within the same experiment coupled with the ability to combine the data to provide an overall solubility assessment for both states. The equilibrium solubility of nine (for consistency and to aid the presented comparisons, drug classification is based on our original paper) BCS class II drugs was investigated: two acids (phenytoin and indomethacin), four bases (aprepitant (aprepitant with a reported p K a of 9.7 at the pH values in this study it will be predominantly un-ionized), tadalafil (tadalafil with a reported p K a value of 15 at the pH values in this study it will be predominantly un-ionized), zafirlukast (zafirlukast with a reported p K a value of 4 will in this system behave as an acidic drug), carvedilol), and three neutral drugs (felodipine, fenofibrate, probucol) and compared to the published fasted and fed DoE studies. The same samples of compounds were employed in the cited published DoE studies , thus eliminating any potential issues associated with the solid state during comparisons.…”
Section: Introductionmentioning
confidence: 99%